2018
DOI: 10.1017/s1463423618000804
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a learning tool for four shoulder tests

Abstract: Aim To analyze the use of YouTube videos as educational tools for four physical examinations of the shoulder: the Neer, Hawkins, empty can, and drop arm tests. Background Video-based education, which is accompanied by text-based education, can be an effective education method, especially in learning medical skills. Medical students and doctors in training often use YouTube videos to share medical education materials, and more systematic review of the reliability of these videos is requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…In conclusion, it was found that information acquired from the Internet was insufficient and sometimes inaccurate [19-22, 25, 29]. Another study reported that significant correlations were observed between the video's usefulness and the uploaded source, as well as between the video's usefulness and viewers' preferences, such as the number of views, views per day, and number of likes [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, it was found that information acquired from the Internet was insufficient and sometimes inaccurate [19-22, 25, 29]. Another study reported that significant correlations were observed between the video's usefulness and the uploaded source, as well as between the video's usefulness and viewers' preferences, such as the number of views, views per day, and number of likes [30].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies state that the information accessed from YouTube is insufficient and that doctors should present an alternative to prevent patients from misinformation [12]. YouTube videos could be used as learning sources for shoulder physical examinations after the application of appropriate filtering processes, such as review of the upload source and viewers' preferences [30].…”
Section: Discussionmentioning
confidence: 99%
“…Inevitably, YouTube™ is used as a source of medical information as one of the largest video resource platforms in the world. Therefore, a large number of studies have assessed the quality of information on YouTube™, such as Schizophrenia, anterior cervical discectomy and fusion, breast self-examination, palliative care education and shoulder tests, but have shown considerable heterogeneity [21][22][23][24][25]. There are mixed reviews of YouTube™ as a source of information.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, medical students and physicians have increasingly turned to YouTube for medical education. Nonetheless, since videos posted on this platform have varying quality and reliability, there is a potential risk of spreading inaccurate information, which can pose a significant challenge in providing optimum healthcare [ 10 ].…”
Section: Introductionmentioning
confidence: 99%